Optically Isotropic State in Bent Core Nematic Mixtures with Rod Like Molecules Induced by Direct Current Electric Field - Hegde, Gurumurthy; Elamain, Omaima; Fodor-Csorba, Katalin; Komitov, Lachezar (AIP Publishing LLC., 2013)
One of the most important characteristic of the liquid crystal displays is the contrast of the generated images. The dark state of the display is a prerequisite for a high image contrast. Optically isotropic state was observed in bent core nematic mixtures containing rod like molecules induced by low applied dc electric field. It is found that the switching properties of these nematic mixtures depend on the concentration of the rod like molecules. Comparatively high concentrations of rod like molecules in the mixtures resulted in an improvement of the contrast and switching properties of the bent core nematic mixtures, thus demonstrating their potential for display applications.